Setting up a cardio thoracic nurse practitioner (NP) program in Pakistan: Challenges encountered and lessons learnt - Jacqueline Maria Dias; Khairunnissa Hooda (Nursing Practice Today, 2018)
Background & Aim: The role of the Nurse Practitioner (NP) is gaining importance worldwide. Many countries in the West and Europe have embraced the role within their health care system. NPs require training to carry out their roles and responsibilities effectively. A one year hospital based certification program was developed for NPs at one University teaching hospital in Pakistan.